Commissary activities and correspondence (1850)
Manuscript records of Commissary activities from 1850-1868, as well as printed correspondence, proclamations and miscellaneous items. Included in the latter are orders to the Commissary from the Adjutant and Inspector General's Office, and a circular from the Governor of Florida, both dated 1864. Includes recording of items confiscated for the use of the Confederate Army.